Evaluating the impact of reducing POFA’s particle fineness on its pozzolanic reactivity and mortar strength - Liew, Yu Xuan; Siti Asmahani, Saad; Anand, N.; Kong, Fah Tee; Chin, Siew Choo (Springer, 2024)
This paper presents the efect of size reduction of palm oil fuel ash (POFA) in the nanoscale to improve the mortar strength. In this work, three diferent particle sizes of POFA prepared using the LA abrasion machine were used as a cement replacement. The physical and chemical properties, mineralogy, and morphology of all POFA specimens were studied. The efect of size reduction on the pozzolanic reactivity of POFA is also studied. The mortar mix design that contained micro and nano POFA was prepared and evaluated for its compressive and fexural properties at the ages of 7, 28, 56, and 90 days. Response surface methodology was used to evaluate the relationship between the factors (cement replacement) and responses (compressive and fexural strength), aiming to fnd the best mix design. The grinding method in this work produced POFA as small as 110 nm. The nano POFAs were observed to have better pozzolanic reactivity compared to micro POFA. The results show that nano POFA increased the mortar strength activity index by up to 20% compared to micro POFA. The best mix design was found using a combination of 10 and 3% of micro and nano POFA as cement replacement. The best mix design shows excellent early compressive strength (7 days) compared to other mixes, although the diference in long-term compressive strength is insignifcant. Similar fndings were observed for the fexural strength, whereby the best mix design was obtained using a combination of 10 and 3% of micro and nano POFA. This work may provide useful insight into the efect of size reduction on the pozzolanic reactivity of POFA.